PENGARUH MEDIA PUZZLE MIPAMI (MITIGASI GEMPA BUMI) TERHADAP KEMAMPUAN KOMUNIKASI LISAN PADA ANAK KELOMPOK B DI TK PURI CENDEKIA IES BENOWO SURABAYA - Nindita Orliana; Mallevi Agustin Ningrum; Novi Anggraeni; Eka Cahya Maulidiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low oral communication skills of group B children at Puri Cendekia Ies Kindergarten Benowo Surabaya, where many children still have difficulty expressing opinions, answering questions, and tend to be passive in class discussions. In addition, the school location has experienced an earthquake disaster requiring learning media that not only stimulates language, but also equips children with disaster mitigation knowledge from an early age. The purpose of this study was to determine the effect of using the Mipami Puzzle media (earthquake mitigation) on children's oral communication skills. This media is designed to introduce the concept of earthquake disaster mitigation through interactive picture-making and storytelling activities. The research method used is quantitative with a Quasi-Experimental design (Nonequivalent Control Group Design). The study population involved all group B children at Puri Cendekia Ies Kindergarten, with a saturated sampling technique that divided subjects into experimental and control groups. Data collection was carried out through observation and tests in the form of pre-tests and post-tests. The results showed a significant effect of the use of the Mipami Puzzle media on improving children's oral communication skills. This is demonstrated through data analysis, which shows a significant difference in average achievement between the experimental and control groups. This media is effective in stimulating children's oral communication skills, including listening skills, asking questions, and conveying ideas or information coherently and clearly.